Emocionalidad política en las veladas de Abraham Valdelomar recorriendo el Perú (1918-1919) - Chaupis Torres, José (2025)
During the Aristocratic Republic, one of the most representative intellectual figures was Abraham Valdelomar (1888-1919). He had a short but intense life developing multiple activities: academic, journalistic, even political. A little-known area was his work as a lecturer at the civic, artistic, and cultural events he organized to gain a deeper understanding of Peru and pedagogically propagate his political and intellectual project, seeking to contribute to the redefinition of the Peruvian identity question and the democratization of the nation-state during his travels across the country between 1918 and 1919. In the first part, we will insert Valdelomar into a broad historicizing contextualization, considering the temporal perspective and articulating it with the sociocultural framework. In the second part, we will address Valdelomar’s political and intellectual project, focusing on the plan of the tours and the structuring of the events. Finally, we will study the lectures given by Valdelomar from the perspective of positive and negative communicative political emotionality, connecting it with the resources of epideictic rhetorical discourse.